2015
DOI: 10.1002/ejlt.201400567
|View full text |Cite
|
Sign up to set email alerts
|

Application of esterase inhibitors: A possible new approach to protect unsaturated fatty acids from ruminal biohydrogenation

Abstract: General nutritional guidelines recommend reducing the consumption of fats originated from ruminant products. This is due to the ruminal biohydrogenation of unsaturated fatty acids (UFAs) which leads to the presence of unhealthy saturated or trans fats in ruminant products. Here, for the first time to our knowledge, we have focused on the main biochemical process which results in the saturation of UFAs. Rumen lipolytic activity (RLA) generates non-esterified fatty acids (NEFAs) in the rumen, which are a prerequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A preliminary study using esterase inhibitors has shown promising results in vitro (Sargolzehi et al . ). Inhibition of ruminal lipase‐producing bacteria using an antilipase antibody affected several lipase‐producing bacteria, including B. fibrisolvens , and decreased BH in vitro (Edwards et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A preliminary study using esterase inhibitors has shown promising results in vitro (Sargolzehi et al . ). Inhibition of ruminal lipase‐producing bacteria using an antilipase antibody affected several lipase‐producing bacteria, including B. fibrisolvens , and decreased BH in vitro (Edwards et al .…”
Section: Discussionmentioning
confidence: 97%
“…Because most dietary FA are glycerides and need lipolysis before BH, decreasing the rumen metabolism of FA could limit rumen BH. A preliminary study using esterase inhibitors has shown promising results in vitro (Sargolzehi et al 2015). Inhibition of ruminal lipase-producing bacteria using an antilipase antibody affected several lipase-producing bacteria, including B. fibrisolvens, and decreased BH in vitro (Edwards et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ruminant products have higher saturated fatty acids (SFA) compared with nonruminants, mainly because of hydrogenation of dietary unsaturated fatty acids by ruminal microbes [1]. Feeding strategies have been developed to increase the unsaturated fatty acids of ruminants' products by increasing the rumen bypass unsaturated fatty acids or decreasing ruminal hydrogenation of dietary unsaturated fatty acids [2]. For ruminants, there are great opportunities to explore the potential of additional forages in their diets.…”
Section: Introductionmentioning
confidence: 99%
“…A new approach to prevent ruminal BH of PUFA, based on the application of esterase inhibitors, has been suggested by Sargolzehi et al . They demonstrated the potential of pyridostigmine bromide, a acetylcholine esterase inhibitor, to reduce rumen lipolytic activity, as no BH of C18:2 n‐6 was observed after 6 h in vitro incubation.…”
Section: Overview Of Existing Rumen Lipid Protection Technologiesmentioning
confidence: 99%